Numerical modeling of the contact effect on the parameters of cracking in a 2D Fatigue Fretting Model - Mohammed Bentahar; Habib Benzaama; Mahmoudi Noureddin (Fracture and Structural Integrity, 2021)
he objective of this work is to study the effects of contact parameters on the cracking parameters of a specimen and a pad assembly. These parameters have been studied and evaluated by the finite element method analysis in two dimensions fretting fatigue model through the Abaqus calculation code. Different values of the coefficient of friction of 0.1, 0.3 and 0.6 were applied on the various lengths in contact for a = 0.1, 0.5 and 1mm. Thus, on the various values of angle of orientation of the crack equal to 15 , 30 and 45 . In addition, elements of the type (CPE4R) and the criterion of maximum tangential stress were applied. The curves of the crack parameters such as the SIF coefficients and the integral J were obtained and discussed.